2021
DOI: 10.1016/j.thromres.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Direct-acting oral anticoagulants use prior to COVID-19 diagnosis and associations with 30-day clinical outcomes

Abstract: Background It is unclear if direct-acting oral anticoagulants (DOACs) use before hospitalization due to COVID-19 diagnosis would potentially impact the severity and clinical outcomes thereafter. We compared 30-day hospitalization/re-hospitalization and clinical outcomes between patients on chronic DOAC therapy and patients not on oral anticoagulation (OAC) therapy at time of COVID-19 diagnosis. Methods We used data from TriNetX, a global federated health research networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
3
20
1
3
Order By: Relevance
“…195 For patients already treated with NOACs or VKA and infected with COVID-19 and particularly in the case of severe infection requiring hospitalization, patients should ideally continue their anticoagulation rather than discontinue, although outcome data are conflicting. 196 197 198 199 …”
Section: Oac Use In Af Patients During the Covid-19 Pandemicmentioning
confidence: 99%
“…195 For patients already treated with NOACs or VKA and infected with COVID-19 and particularly in the case of severe infection requiring hospitalization, patients should ideally continue their anticoagulation rather than discontinue, although outcome data are conflicting. 196 197 198 199 …”
Section: Oac Use In Af Patients During the Covid-19 Pandemicmentioning
confidence: 99%
“… 13 One RCT and two cohort studies on antiplatelet agents and oral anticoagulants did not demonstrate any benefit of prescribing these agents after diagnosis of COVID‐19. 9 , 10 , 11 A single study that used a randomized control design, showed that the glycosaminoglycan oral drug sulodexide may reduce risk of hospitalization and possibly also the need for oxygen supplementation. 12 These results need to be confirmed in future studies.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“… 17 Two large cohort studies of outpatients with cardiovascular disease, who were mostly on direct oral anticoagulants (DOACs), did not show reduced risk of hospitalization, death, or thrombosis. 10 , 11 However, in the larger of the two studies, no minimum exposure to outpatient oral anticoagulation was required, nor was there adjustment for in‐hospital treatments. 10 A population‐based outpatient cohort study found a small increase in mortality risk among those on pre‐existing oral anticoagulation, but there was no adjustment for in‐hospital treatments or antithrombotic regimen modification.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“… 307 For patients already treated with NOACs or VKA are infected with COVID‐19 and particularly in case of severe infection requiring hospitalization, patients should ideally continue their anticoagulation rather than discontinue, although outcome data are conflicting. 308 , 309 , 310 , 311…”
Section: Oac Use In Patients With Atrial Fibrillation During the “Coronavirus Disease 2019” ( Covid ‐19) Pandmentioning
confidence: 99%